Palm Oil - Waisundara, Viduranga (IntechOpen, 2018)
Palm oil production is one of the most developed and noteworthy industries in the world, leading to rapid economic growth in countries where the industry has been established. Currently, palm oil is the world's leader in the vegetable oil industry with a yearly production and consumption of approximately 45.3 million tons, which almost covers 60% of the global trade of vegetable oils in the international market. Along these lines, it is expected that the global demand for palm oil will be doubled by 2020. The book focuses on various aspects of palm oil production, primarily, the environmental aspects, its application as an animal feed, chemical and nutritional properties of the oil, and technical aspects of enhancing the efficacy of production.